LOCAL THERAPY MANAGEMENT OF ORAL PATHOLOGY IN PATIENTS WITH FIXED ORTHODONTIC APPLIANCES DURING THE COVID -19 PANDEMIC - Mioara Decusară; Daniela Cornea; Carmen Tiutiuca; Alina Ramona Dimofte; Gabi Topor; Denisa Batir Marin; Gabriela-Violeta Iordăchiță (Romanian Society of Oral Rehabilitation, 2022)
In this article we will present some aspects of the therapeutic approach to gingival inflammation and lesions of oral mucosa during the 2 months of lockdown, considering the protocols on the spread of SARS-coV-19 virus. We used local therapeutic medication for oral pathology in patients with fixed orthodontic, avoiding as much as possible of therapeutic methods which were at risk of spreading COVID-19 infection. To prevent and limit SARS-CoV-2 Coronavirus contamination before and at the end of orthodontic treatment, the patient rinses the mouth for at least 30 seconds with 1% - 1.5% hydrogen peroxide or iodine antiseptic solutions. povidone 0.2% - 1% (7,8).